Developing highly conducting and mechanically durable styrene butadiene rubber composites with tailored microstructural properties by a green approach using ionic liquid modified MWCNTs. Issue 39 (1st April 2016) - Abraham, Jiji; P., Mohammed Arif; Kailas, Lekshmi; Kalarikkal, Nandakumar; George, Soney C.; Thomas, Sabu
Abstract : Present paper is focussed on the fabrication of styrene-butadiene rubber–ionic liquid modified CNT nano composites by using a more sustainable chemistry and a clean process with the use of a green solvent ionic liquid. Abstract : We report the effect of surface modification of multi-walled carbon nanotubes (MWCNTs) by an ionic liquid, 1-ethyl-2, 3-dimethylimidazolium bis(trifluoromethylsulfonyl). An apparent physical (cation–π/π–π) interaction between the ionic liquid and MWCNTs was revealed by Raman and UV-visible spectroscopies. The composite loaded with 10 phr MWCNTs exhibits impressive enhancements in tensile strength (381% increase), hardness (34% increase), and abrasion resistance. High electrical conductivity was also achieved at MWCNT loading levels beyond 3 phr loading, with a low percolation threshold (0.023 vol%) for the composites. The microstructural development of conductive networks and uniform dispersion of MWCNTs in the presence of ionic liquid were analysed by TEM and AFM. The experimentally observed mechanical and electrical properties have been compared with theoretical predictions, and confirm that the dramatic improvement in mechanics and electrical conductivity is the outcome of the extremely fine dispersion, the strong secondary network of MWCNTs and improved interaction at the interface via thermodynamically-induced adsorption and physical interlocking of polymer chains in the nanoscopic MWCNT structure. This study demonstrates a simplified and eco-friendly approach to develop multifunctional advanced materials based on ionic liquid modified MWCNT elastomer composites with a much better balance among mechanical properties, conductivity and filler content.